IMPACTO DA DIMENSÃO GESTAÇÃO SAUDÁVEL E SEGURA DO PROJETO CUIDANDO DO FUTURO NAS AÇÕES DE PRÉ-NATAL E NA REDUÇÃO DA MORTALIDADE INFANTIL NO MUNICÍPIO DE BACABAL-MA - Pereira, Wédia Duarte (2014)
The actions developed to promote a healthy and safe pregnancy promote a decline in infant mortality in many regions of the country, the adoption of educational practices and investment in improving the quality of services, but is, therefore, being necessary to implement programs improvement to ensure quality care. Thus, the present study aimed to evaluate the actions of prenatal developed before and after the implementation of the Project Caring for the Future, in the municipality of Bacabal, considering the indicators under the dimension Healthy Pregnancy and Safe. This is a descriptive study with a quantitative approach, developed in Bacabal, Maranhao, from data SISPRENATAL, pregnant women who started and finished the prenatal care in the years 2009 and 2011, one year before the implementation of the Project Caring for the Future and one year, respectively, based on the quality indicators proposed by the Project Caring for the Future. To study the indicator of infant mortality, we used data from the Mortality Information System and Information System of Live Birth and analyzed by Statistical Package for the Social Sciences software, using Pearson's correlation to compare the variables under study. It was observed that the number of pregnant women who received seven or more increased from 1.2% to 14.7%, noting an increase in achievement of prenatal care in the first quarter from 11.7% to 66.5%. Regarding laboratory tests, in 2009, 10% of pregnant women underwent all tests, with an increase to 13% in 2011 and the number of pregnant women immunized expanded from 51.6% to 79%. With all of these indicators improved, there was a reduction in infant mortality. We conclude that the Caring Project of the Future had a positive impact on the actions of prenatal care, helping to reduce the infant mortality rate, making it a challenge currently investing more in policies and practices to proper prenatal care, improving increasing the quality indicators and further reducing child mortality.